IMPERIO INCA ¿UN PODEROSO ESTADO? - Choquehuanca Luque, Milner Jesus (Facultad de Ciencias Jurídicas y Políticas - Universidad Nacional del Altiplano de Puno, 2023)
This work establishes a relationship between the organization system and the construction of a multiethnic State under certain reasons behind the Inca expansion. Therefore, this essay aims to substantiate that the Incas formed a State, under the various requirements or essential elements therefore it requires. TheInca culture is studied and analyzed by historians, sociologists, anthropologists, etc. who throughout history tried to find out and interpret the various vestiges and the reason for their expansion and organization, as well as the form and type of government in the empire, which resemble the form of Roman government, omnipotent and centralist with a close cosmological, theological, blood bond. A sovereign State, with a high power over the population (ayllus) and the other ethnic groups absorbed by two modalities: by a peaceful way (respecting their culture and language) and by another violent and ruthless (imposing their culture and language).